2014
DOI: 10.21101/cejph.a4010
|View full text |Cite
|
Sign up to set email alerts
|

Seroprevalence of Rubella Antibodies among Adult Egyptian Females Aged 20-30 Years. Is there a Need for Rubella Vaccination?

Abstract: SUMMARYIntroduction: Egypt adopted a comprehensive strategy to eliminate measles and rubella by conducting a catch up campaign (in 2008) targeting children and young adults in the age group 10-19 years. This study aimed to explore the seroprevalence of rubella among females aged 20 to 30 years in order to provide the Ministry of Health with information to develop future strategies for rubella supplemental immunization activities among women of childbearing age before marriage and conception.Methods: A total of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
13
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(17 citation statements)
references
References 21 publications
3
13
0
Order By: Relevance
“…Our findings showed that marital status was an insignificant predictor of Rubella seropositivity. This result corroborates with the study carried out among Egyptian females [30].…”
Section: Discussionsupporting
confidence: 93%
“…Our findings showed that marital status was an insignificant predictor of Rubella seropositivity. This result corroborates with the study carried out among Egyptian females [30].…”
Section: Discussionsupporting
confidence: 93%
“…Also, Olajide et al, 19 registered the illiterate and primary school females showing completely (100%) IgG-positive while the secondary and tertiary ranging from 90% to 93.2%. Conversely, Gadallah et al, 22 illustrated the university grade and primary to secondary school individuals show nearly similar antirubella prevalence and no significant differences. The variation in previous results to this result may be referred to as many factors that play a minor role in rubella virus infection.…”
Section: Discussionmentioning
confidence: 94%
“…The incidence of rubella infection through the first trimester or second trimester represents a risk for the developing fetus resulting in congenital rubella syndrome Conversely, a study by Sallam et al,8 observed that the participants from the rural area had a higher prevalence rate of rubella IgG antibody than the urban area. Also, Gadallah et al, 22 noticed that the participants belong to a rural area having a high rate than participated women coming from an urban area. Olajide et al, 19 found that the prevalence rate of rubella IgG was 93.8% and 90.3% in urban and rural areas, respectively.…”
Section: Discussionmentioning
confidence: 99%
“…Concerning history of rubella infection, the existing study report that 2.3% of pregnant women had a history of rubella infection, but Esposito et al, [15] found the percent was 15% this difference come from the group of people that the study applied on, as this study performed on pregnant women only, but Mohsen et al [16] accomplished his study on all female aged from 20-30 years in Egypt. In addition, there was relation between pre test score of knowledge and history of rubella in previous pregnancy.…”
Section: Discussionmentioning
confidence: 85%